Individual Psychology as Represented By Joel In Love And Monster Film (2020) - Christyanti, Irene Jessica; Arifin, M Bahri; Max, Jonathan Irene Sartika Dewi (Fakultas Ilmu Budaya Universitas Mulawarman, 2024)
This research focuses on analyzing the character of Joel Dawson in the film Love and Monsters, directed by Michael Matthews, through the lens of Alfred Adler's individual psychology. This research applied a descriptive qualitative method. This research applied the theory of characterization by Petrie and Boggs to draw conclusions about the character's individual psychology. The results obtained by the researcher in this research are the five aspects of individual psychology, such as inferiority feeling, fictional finalism, striving for superiority, creative self, and style of life.